1996
DOI: 10.2307/3345666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempo on Music Preferences of Children in Elementary and Middle School

Abstract: This study was designed to examine the effect of tempo on preference responses of kindergarten to Grade 8 children. Listener age and gender were additional variables under consideration. In total, 996 subjects indicated preference opinions on pictographic Likert written response forms while listening to 15 excerpts of orchestral music from early Romantic opera. Two moderate and three fast musical examples were given the highest mean ratings. Spearman rank correlation indicated a positive significant relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
4
23
0
4
Order By: Relevance
“…According to the literature, quick music-tempo is more appealing to preschool children evoking a happy tone (Dalla Bella et al, 2001;Flowers, 1988;LeBlank, Colman, McCrary, Sherrill, & Malin, 1988;Montgomery, 1996). A slow tempo tends to evoke a sad tone (Balkwill & Thompson, 1999;Gabrielsson & Juslin, 1996;Juslin, 1997;Peretz, Gagnon, & Bouchard, 1998).…”
Section: The Music Used In the Researchmentioning
confidence: 99%
“…According to the literature, quick music-tempo is more appealing to preschool children evoking a happy tone (Dalla Bella et al, 2001;Flowers, 1988;LeBlank, Colman, McCrary, Sherrill, & Malin, 1988;Montgomery, 1996). A slow tempo tends to evoke a sad tone (Balkwill & Thompson, 1999;Gabrielsson & Juslin, 1996;Juslin, 1997;Peretz, Gagnon, & Bouchard, 1998).…”
Section: The Music Used In the Researchmentioning
confidence: 99%
“…Postoji velik broj istraživanja koja se bave povezanošću različitih glazbeno-izražajnih sastavnica, poput tempa, dinamike, izvođača, ritma, melodije i ugođaja, s glazbenim preferencijama sudionika (LeBlanc, 1981;LeBlanc i McCrary, 1983;Flowers, 1988;Montgomery, 1996;Dobrota i Reić Ercegovac, 2009). Mali broj istraživanja bavio se preferencijama učenika prema narodnoj glazbi.…”
Section: Uvod*unclassified
“…Regardless of the genre, listeners, particularly school-aged children, are drawn to music of faster tempi (Montgomery, 1996;LeBlanc, Young, Simpson, Stamou, & McCrary, 1998;LeBlanc, 1981). This preference towards faster music can be seen in quantitative studies as well as in both written reflective comments and physical observation during testing.…”
Section: Physical Characteristics Of Musicmentioning
confidence: 99%
“…A LeBlanc et al study (1998) found not only that tempo was the most frequently cited element (accounting for 32% of all comments), but that 91% of comments regarding tempo from an administered preference index claimed they either liked the fast songs because of the tempo or reversely, did not like the slow selections as a result of the tempo. Montgomery (1996) also noted that tempo becomes a higher priority in preference decisions starting between second and third grade, potentially as a result of the influence of popular music in his or her daily lives.…”
Section: Physical Characteristics Of Musicmentioning
confidence: 99%
See 1 more Smart Citation